Misframed ubiquitin and impaired protein quality control: an early event in Alzheimer’s disease - Gentier, Romina J.; van Leeuwen, Fred W. (Frontiers in Molecular Neuroscience, 2015)
Aβ plaque formation is a prominent cellular hallmark of Alzheimer’s disease (AD). To date, immunization trials in AD patients have not been effective in terms of curing or ameliorating dementia. In addition, γ-secretase inhibitor strategies await clinical improvements in AD. These approaches were based upon the idea that autosomal dominant mutations in amyloid precursor protein and Presenilin 1 genes are predictive for treatment of all AD patients. However most AD patients are of the sporadic form which partly explains the failures to treat this multifactorial disease. The major risk factor for developing sporadic AD is aging whereas the ε4 polymorphism is the most prominent genetic risk factor. Other medium-risk factors such as TREM 2 and nine low risk factors from Genome Wide Association Studies (GWAS) were associated with AD. Recently, pooled GWAS studies identified protein ubiquitination as one of the key modulators of AD. In addition, a brain site specific strategy was used to compare the proteomes of AD patients by an Ingenuity Pathway Analysis. This strategy revealed numerous proteins that strongly interact with ubiquitin signaling, and pointing to a dysfunctional ubiquitin proteasome system (UPS) as a causal factor in AD. We reported that DNA-RNA sequence differences in several genes including ubiquitin do occur in AD, the resulting misframed protein of which accumulates in the cellular hallmarks of AD. This suggests again a functional link between neurodegeneration of the AD type and loss of protein quality control by the UPS. Progress in this field is discussed and modulating the activity of the UPS opens an attractive avenue of research towards slowing down the development of AD and ameliorating its effects by discovering prime targets for AD therapeutics.